Efektivitas Multimedia terhadap Pembelajaran Penjas di Sekolah Dasar : Literatur Review - Asep Marpu; Cucu Hidayat; Juhrodin Juhrodin (Universitas Galuh, 2026)
ABSTRACTThis study aims to analyze the effectiveness of multimedia in Physical Education learning at the elementary school level through a narrative literature review of 15 selected articles published between 2010 and 2025. The synthesis indicates that various forms of multimedia—including audiovisual materials, interactive videos, educational websites, PowToon animations, and Construct 2 applications—consistently enhance students’ motor skills, learning motivation, and understanding of movement techniques. Clear visual representations, the ability to replay content, and integrated audio–visual formats enable students to learn sports techniques more accurately than through conventional teacher demonstrations. Moreover, multimedia creates engaging learning experiences that align with the developmental characteristics of young learners, thereby increasing attention, interest, and participation. However, most previous studies focus only on short-term effects, employ quasi-experimental designs, and utilize relatively basic multimedia technologies. Therefore, further research is needed to incorporate advanced technologies such as AR/VR, conduct long-term evaluations, and develop multimedia systems with automatic feedback features to support the transformation of Physical Education learning in line with the Merdeka Curriculum. Keywords: Multimedia; Physical Education; Elementary School ABSTRAKPenelitian ini bertujuan menganalisis efektivitas multimedia dalam pembelajaran Pendidikan Jasmani di Sekolah Dasar melalui literature review naratif terhadap 15 artikel terpilih dari tahun 2010–2025. Hasil sintesis menunjukkan bahwa multimedia—meliputi audiovisual, video interaktif, website pembelajaran, PowToon, dan Construct 2—secara konsisten meningkatkan keterampilan motorik, motivasi belajar, serta pemahaman teknik gerak siswa SD. Representasi visual yang jelas, kemampuan pengulangan materi, serta integrasi audio–visual memungkinkan siswa mempelajari teknik olahraga dengan lebih akurat dibanding metode demonstrasi konvensional. Selain itu, multimedia menciptakan pengalaman belajar yang menarik dan sesuai dengan karakteristik perkembangan anak, sehingga meningkatkan perhatian, minat, dan partisipasi siswa. Kendati demikian, penelitian sebelumnya masih terbatas pada dampak jangka pendek dan teknologi sederhana, serta didominasi desain quasi-eksperimen. Oleh karena itu, diperlukan penelitian lanjutan yang mengintegrasikan teknologi mutakhir seperti AR/VR, evaluasi jangka panjang, serta pengembangan multimedia dengan fitur umpan balik otomatis untuk mendukung transformasi pembelajaran PJOK sesuai tuntutan Kurikulum Merdeka. Kata Kunci: Multimedia,Pendidikan Jasmani, Sekolah Dasar